Security fungibility and the cost of capital: evidence from global bonds - Darius P. Miller; John J. Puthenpurackal (European Central Bank (ECB), 2005)
This paper examines the potential benefits of security fungibility by conducting the first comprehensive analysis of Global bonds. Unlike other debt securities, Global bonds' fungibility allows them to be placed simultaneously in bond markets around the world; they trade, clear and settle efficiently within as well as across markets. We test the impact of issuing these securities on firms' cost of capital, issuing costs, liquidity and shareholder wealth. Using a sample of 230 Global bond issues by 94 companies from the U.S. and abroad over the period 1996-2003, we find that firms are able to lower their cost of (debt) capital by issuing these fungible securities. We also document that the stock price reaction to the announcement of Global bond issuance is positive and significant, while comparable domestic and Eurobond issues over the same time period are associated with insignificant changes in shareholder wealth.
Keywords: F3; G1; G3; 330; cost of capital; Global bonds; international capital raising; security fungibility; Internationale Anleihe; Kapitalkosten; Schätzung; USA